QUATERNARY HISTORY OF CEDRUS IN SOUTHERN EUROPE - Magri, D. (Annali di Botanica, 2012)
A database of 68 pollen records of Pleistocene age was compiled from the western Mediterranean regions, with the aim of reconstructing the history of Cedrus in south Europe during the last 2 Ma. Marine pollen records from the Alboran Sea suggest that Cedrus was present in Morocco throughout the Quaternary, while it was absent from the Iberian peninsula, except a possible local presence in a coastal site of southern Spain. In France, Cedrus pollen was recorded in Pliocene deposits, but its Quaternary finds are always very sparse and suggest a long distance origin of cedar pollen. Cedrus was widespread in all the Italian sites during the Early Pleistocene, but it is sporadically found in the Middle Pleistocene deposits. Although times and modes of the disappearance of Cedrus from Italy are not known, it appears that the marked climate changes occurred between 0.9 and 0.7 Ma determined its local extinction. A similar trend is found in Greece, where Cedrus may have persisted a little longer than in the Italian Peninsula. On the whole, the history of Cedrus in southern Europe indicates that it is a taxon vulnerable to global climate changes and warns of a future risk of extinction also in the rest of the Mediterranean Basin.